Mapping of the Coronavirus Circulating in Asia Based on Sequence of Gene Spike and Membrane Protein Used MEGA-X Aplication - Rell, Fedri; Jalil, Muhammad Fikri Raditya; Husada, Anggini Putri; Dariming, Nur Azizah (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2022)
Coronavirus are viruses that can be transmitted to human and animals. Severe acute respiratory syndrome, middle east respiratory syndrome, and Coronavirus disease 2019 are disease can be caused by several subtypes of coronavirus.  The aims of this study were to mapping of the coronavirus circulating in Asia based on sequence of gene spike and membrane protein virus. Totally of 67 coronavirus spike protein and membrane gene sequence were accessed via GenBank® (www.ncbi.nlm.nih.gov/genbank/) matched with the ClustalW Method MEGA-X. The result of the study are 20 groups of coronavirus were found based on spike protein gene sequences and 27 groups of coronavirus were found based on membrane protein gene sequences which were different with the first group of coronavirus found in Wuhan. Therefore, it can be concluded that the coronavirus circulate in several Asian countries had been mutate on gene spike and membrane protein. Keywords: Asia, Coronavirus, MEGA-X, Membrane Protein, Spike Protein